Employee, satisfaction with national health insurance scheme at the University of Ibadan (2014)
"The study investigated the factors that lead to employees' satisfaction with the services of the University health services as vendors of the National Health Insurance Scheme (NHS) in the University of Ibadan, Nigeria. A descriptive survey research design was used for the study. The study population was made up of both academic and non-academic staff of the University. A sample size of 225 was selected though simple random sampling technique. Data was collected by the use of questionnaire and in-depth interviews. The questionnaire which comprised of open and closed ended questions were administered to the respondents. A total of 8 in-depth interviews were conducted across eight randomly selected areas for the study. The quantitative data generated through the questionnaire were analyzed at the univariate and bivariate levels employing frequency distribution and percentages. The resulting qualitative data was analyzed using manual content analysis to enhance the explanatory clarity of the findings. Findings show that there was heightened awareness of the scheme amount the employees. Majority of the employees claimed that they were satisfied with the Health Care Service provided under NHIS. The study revealed that the employees encountered some challenges with the scheme such as long waiting time before obtaining their registration cards and also before consultation with the doctors. The study also showed that there was need for improvement in the services provided to the enrollees in the benefit package of the scheme. In order to maintain satisfactory health care service for the employees, it was recommended that government should organize stakeholder's forum where joints needs assessment could be done. This will go a long way in ensuring that the employees continue to enjoy satisfactory health care services. "